Working Globally: Advancing International Competencies in Counseling Psychology. (May 2019) - Nilsson, Johanna E.; Wang, Li-fei; Chung, Y. Barry
This major contribution presents results from a presidential initiative undertaken by Y. Barry Chung during his year as the president of the Society of Counseling Psychology to advance cross-cultural collaboration and promote understanding of international competencies in psychology. This initiative brought together 72 psychological professionals from 23 countries to address issues salient to the global field of counseling psychology. We utilized two models of international competencies to frame these issues, namely the dynamic-systemic-process model of international competencies and the cross-national cultural competence model. The introductory article reviews international efforts in counseling psychology and provides an overview of the three subsequent articles. The second article addresses how historical, economic, and sociopolitical events have shaped the development of counseling psychology in different countries. The third article discusses social justice competencies from an international perspective, and the fourth article focuses on development of competencies for international disaster mental health work.